Integrating a Triboelectric Nanogenerator and a Zinc‐Ion Battery on a Designed Flexible 3D Spacer Fabric. Issue 10 (20th July 2018) - Wang, Zifeng; Ruan, Zhaoheng; Ng, Wing Sum; Li, Hongfei; Tang, Zijie; Liu, Zhuoxin; Wang, Yukun; Hu, Hong; Zhi, Chunyi
Abstract: Powering flexible electronics by wearable energy‐storage or energy‐harvesting devices has attracted enormous research interest recently. However, the continual powering offered by individual energy‐storage devices, such as rechargeable batteries or supercapacitors, becomes problematic once the energy stored is fully discharged. Therefore, the integration of energy‐storage and energy‐harvesting techniques becomes a feasible approach to provide a continual power supply for flexible and wearable electronics. Herein, an integrated flexible and wearable triboelectric nanogenerator (TENG) and rechargeable Zn‐ion battery (ZIB) system based on a flexible 3D spacer fabric is proposed as a promising wearable power unit for powering personal electronic devices. The energy harvested by the TENG from human motion can be utilized to refill the ZIB once its stored energy is exhausted. Moreover, the power unit can be easily scaled up to multipixel, due to the compatibility of the fabric with the textile industry, which renders the system with promise as a practical wearable personal power station in the future. Abstract : The integration of a triboelectric nanogenerator (TENG) and a flexible rechargeable Zn‐ion battery is realized on a piece of specially designed 3D spacer fabric, from which the electricity generated from mechanical energy by the TENG can be used to charge the flexible battery for powering electronic devices.